Proportions of and trends in exposure to pro-tobacco and anti-tobacco advertisements among young adolescents aged 12-16 years in 142 countries and territories, 1999-2018: an analysis of repeated cross-sectional surveys - Ma Chuanwei; Yang Hui; Sun Jiahong; Zhao Min; Magnussen Costan G; Xi Bo (Netherlands, 2026)
Background
The proportions and trends in exposure to pro-tobacco and anti-tobacco advertisements among young people remain unknown globally. We determined recent (2010–18) proportions of exposure to pro-tobacco and anti-tobacco advertisements among young adolescents and their secular trends from 1999 to 2018.
Methods
In this analysis of repeated cross-sectional surveys, we used the most recent data from 142 countries and territories (hereafter referred to as countries) collected between Jan 1, 2010, and Dec 31, 2018, comprising 710 191 participants, to assess the proportions of exposure to pro-tobacco and anti-tobacco advertisements among young adolescents aged 12–16 years. Data from 120 countries that had performed two or more Global Youth Tobacco Surveys between Jan 1, 1999, and Dec 31, 2018, comprising 1 482 031 participants, were used to assess trends in the proportions of exposure to pro-tobacco and anti-tobacco advertisements over time. A χ2 test analysis was used for proportion comparisons between subgroups. Exposure to pro-tobacco and anti-tobacco advertisements were calculated as proportions using sampling weights, strata, and primary sampling units.
Findings
The most recent global proportion of past 30-day exposure to tobacco advertisements among young adolescents was 433 585 (64·6%) of 710 191 (95% CI 63·5–65·7; all final percentages were weighted) for messages on electronic media, 206 766 (33·1%) of 710 191 (31·9–34·4) for exposure at the point of sale, and 63 385 (10·2%) of 710 191 (9·7–10·6) for owning something with a tobacco brand logo. The most recent global proportion of exposure to anti-tobacco advertisements was 431 862 (63·6%) of 710 191 (62·3–64·9) for messages on electronic media and 227 658 (34·1%) of 710 191 (32·8–35·3) for exposure to gathering activities. The majority of included countries showed a decreasing trend in exposure to tobacco advertisements (111 [93%] of 120) and anti-tobacco advertisements (110 [92%] of 120) between 1999 and 2018.
Interpretation
Among young adolescents, exposure to tobacco advertisements remains high, and exposure to anti-tobacco advertisements is not high enough. The proportion of young adolescents exposed to pro-tobacco and anti-tobacco advertisements had decreased over time in the majority of included countries. These findings underscore the importance of strict implementation of regulation on tobacco control including strengthening anti-tobacco marketing and prohibiting tobacco marketing.